Comparison of Signaling Pathways Gene Expression in CD34− Umbilical Cord Blood and Bone Marrow Stem Cells - Rafał Stojko; Monika Bojdys-Szyndlar; Agnieszka Drosdzol-Cop; Andrzej Madej; Krzysztof Wilk (Hindawi Limited, 2016)
The aim of the study was to compare the biological activity of the total pool of genes in CD34− umbilical cord blood and bone marrow stem cells and to search for the differences in signaling pathway gene expression responsible for the biological processes. The introductory analysis revealed a big similarity of gene expression among stem cells. When analyzing GO terms for biological processes, we observed an increased activity of JAK-STAT signaling pathway, calcium-mediated, cytokine-mediated, integrin-mediated signaling pathway, and MAPK in a cluster of upregulating genes in CD34− umbilical cord blood stem cells. At the same time, we observed a decreased activity of BMP signaling pathways, TGF-beta pathway, and VEGF receptor signaling pathway in a cluster of downregulating genes in CD34− umbilical cord blood stem cells. In accordance with KEGG classification, the cytokine-cytokine receptor interaction, toll-like receptor signaling pathway, and JAK-STAT signaling pathway are overrepresented in CD34− umbilical cord blood stem cells. A similar gene expression in both CD34− UCB and BM stem cells was characteristic for such biological processes as cell division, cell cycle gene expression, mitosis, telomere maintenance with telomerase, RNA and DNA treatment processes during cell division, and similar genes activity of Notch and Wnt signaling pathways.